Calcium imaging in freely moving mice during electrical stimulation of deep brain structures. (26th February 2021) - Trevathan, James K; Asp, Anders J; Nicolai, Evan N; Trevathan, Jonathan M; Kremer, Nicholas A; Kozai, Takashi DY; Cheng, David; Schachter, Mike J; Nassi, Jonathan J; Otte, Stephani L; Parker, Jones G; Lujan, J Luis; et al.
Abstract: Objective . After decades of study in humans and animal models, there remains a lack of consensus regarding how the action of electrical stimulation on neuronal and non-neuronal elements—e.g. neuropil, cell bodies, glial cells, etc.—leads to the therapeutic effects of neuromodulation therapies. To further our understanding of neuromodulation therapies, there is a critical need for novel methodological approaches using state-of-the-art neuroscience tools to study neuromodulation therapy in preclinical models of disease. Approach . In this manuscript we outline one such approach combining chronic behaving single-photon microendoscope recordings in a pathological mouse model with electrical stimulation of a common deep brain stimulation (DBS) target. We describe in detail the steps necessary to realize this approach, as well as discuss key considerations for extending this experimental paradigm to other DBS targets for different therapeutic indications. Additionally, we make recommendations from our experience on implementing and validating the required combination of procedures that includes: the induction of a pathological model (6-hydroxy dopamine model of Parkinson's disease) through an injection procedure, the injection of the viral vector to induce GCaMP expression, the implantation of the gradient refractive index lens and stimulation electrode, and the installation of a baseplate for mounting the microendoscope. We proactively identify unique data analysis confounds occurring due to the combination of electrical stimulation and optical recordings and outline an approach to address these confounds. Main results . In order to validate the technical feasibility of this unique combination of experimental methods, we present data to demonstrate that (1) despite the complex multifaceted surgical procedures, chronic optical recordings of hundreds of cells combined with stimulation is achievable over week long periods (2) this approach enables measurement of differences in DBS evoked neural activity between anesthetized and awake conditions and (3) this combination of techniques can be used to measure electrical stimulation induced changes in neural activity during behavior in a pathological mouse model. Significance . These findings are presented to underscore the feasibility and potential utility of minimally constrained optical recordings to elucidate the mechanisms of DBS therapies in animal models of disease.